Salmeterol/fluticasone stable-dose treatment compared with formoterol/budesonide adjustable maintenance dosing: impact on health-related quality of life - Price, David B (BioMed Central, 2007)
BACKGROUND: Improving patients' health-related quality of life (HRQoL) is recognized as a fundamental part of asthma management. The aims of this study were to evaluate the long-term efficacy (including symptom-free days and exacerbations) and impact on HRQoL of a stable-dose regimen of salmeterol/fluticasone propionate (SAL/FP) and an adjustable maintenance dosing (AMD) regimen of formoterol/budesonide (FOR/BUD) where treatment is adjusted based on symptoms [SAM40056]. METHODS: A total of 688 outpatients with asthma receiving regular low-dose inhaled corticosteroids (ICS) plus a long-acting β(2)-agonist, or medium dose ICS alone participated in this randomized, double-blind, double-dummy, parallel-group, 1-year trial, which was conducted in 91 centers in 15 countries. Patients were randomized to receive 1 inhalation of SAL/FP 50/250 μg BID or 2 inhalations of FOR/BUD 6/200 μg BID during Weeks 1–4. For Weeks 5–52, patients meeting strict continuation criteria for stable asthma at Week 4 received AMD with FOR/BUD or stable-dose SAL/FP. RESULTS: The percentage of symptom-free days was significantly greater (58.8% vs 52.1%; p = 0.034) and the annual exacerbation rate was significantly lower (47%; p = 0.008) with stable-dose SAL/FP compared with FOR/BUD AMD. A total of 568 patients completed the Asthma Quality of Life Questionnaire (AQLQ) at least once during the study. The mean change from baseline in AQLQ overall score was numerically greater with SAL/FP than FOR/BUD at week 28 and week 52, but did not reach statistical significance (p = 0.121 at Week 52). However, in a post hoc logistic regression analyses for any AQLQ improvement, significant benefits with SAL/FP were seen at both time points (p = 0.038 and p = 0.009, respectively). The minimally important difference of ≥ 0.5-point improvement in AQLQ overall score was achieved by a significantly greater number of patients receiving SAL/FP at Week 28 (68% vs 60%; p = 0.049); a trend for this difference remained at Week 52 (71% vs 65%) (p = 0.205). CONCLUSION: In this population of patients with persistent asthma, stable-dose SAL/FP resulted in significantly greater increases in symptom-free days, a reduction in exacerbation rates, and provided greater HRQoL benefits compared with FOR/BUD AMD. TRIAL REGISTRATION: Clinical Trials registration number NCT00479739